2001
DOI: 10.1002/1521-396x(200105)185:1<15::aid-pssa15>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

SiC Based Field Effect Gas Sensors for Industrial Applications

Abstract: The development and field-testing of high-temperature sensors based on silicon carbide devices have shown promising results in several application areas. Silicon carbide based field-effect sensors can be operated over a large temperature range, 100-600 C, and since silicon carbide is a chemically very inert material these sensors can be used in environments like exhaust gases and flue gases from boilers. The sensors respond to reducing gases like hydrogen, hydrocarbons and carbon monoxide. The use of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 14 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…This limits sensor operation temperatures of SiMOS devices to temperatures less than 200 • C. In order to overcome such limitations, catalytic gate devices were later also produced on SiC [8][9][10] and GaN [11][12][13] substrates.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…This limits sensor operation temperatures of SiMOS devices to temperatures less than 200 • C. In order to overcome such limitations, catalytic gate devices were later also produced on SiC [8][9][10] and GaN [11][12][13] substrates.…”
Section: Introductionmentioning
confidence: 56%
“…In recent papers [25,26], we have shown that the gas sensing capabilities of SiMOS capacitors can be extended to the same range of hydrocarbon species, which previously could only be detected using high-temperature-operated SiC-or GaN-based MOS devices [8][9][10][11][12][13]. The way to achieve this is operating the SiMOS devices in a pulsed-temperature mode in which high-temperature chemical sampling interchanges with low-temperature electrical read-out of the C-V characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The voltage shift of the I ( V ) curve (where I =const.) is the sensor signal 28 . Sensors have been successfully tested in real exhaust gas.…”
Section: Ammonia Sensorsmentioning
confidence: 99%
“…2,5,6 Figure 1 shows a schematic diagram of a typical device. Such devices have been successfully demonstrated for monitoring automotive exhaust, 7,8 flue gases from power plants, [9][10][11] and selective catalytic reduction in diesel engines. 12 Our understanding of the sensing mechanism is based largely on the pioneering work of Lundström and co-workers, [13][14][15][16][17][18][19] Kreisl et al, 20,21 and Salomonsson et al 22 on similar silicon-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…7,24 In the present studies, unlike those conducted by other groups, 9,11,12,24 the gates were continuous, nonporous gates in direct contact with the oxide, 32 so these extra processes do not arise. In particular, direct adsorption of oxygen on the oxide surface, which has been proposed as an important mechanism for porous-gate devices, 24 is not significant for the sensors studied here.…”
Section: Introductionmentioning
confidence: 99%